Formation of Novice Business Students' Mental Models Through Simulation Gaming. (December 2013) - Palmunen, Lauri-Matti; Pelto, Elina; Paalumäki, Anni; Lainema, Timo
Studies on students' perceptions of learning in business simulations often suggest that students like simulations and view them more positively than both lectures and case discussions. However, research on the actual learning outcomes deriving from participating in business simulations still needs to be pursued. Consequently, the purpose of this case-study article is to examine how a business simulation game contributes to the cognitive learning of novices in business studies. We describe the use of a clock-driven business simulation for teaching 133 novices in business studies at the University of Turku, Finland. The students' cognitive learning was evaluated based on data generated by pre- and post-game concept map tests designed to illustrate the formation and change of mental models during the simulation course. The results of this study suggest that simulation games can provide a solid basis for novice learning. They help to increase comprehension of the complexity of business organizations and the various processes, transactions, and operations involved.